Commodification and Exploitation of Children in Television Content Programs and New Media Content (Case Study of Fajar Labatjo Alias Fajar Sadboy) - Noor, M. Arifin Ritani (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Cases of commodification of children are increasingly common, various television programs and online media have shown many children who are considered viral. The television and online industries take advantage of the child's virality value to be converted into exchange rates. Commodification, which is a term that refers to the practice of converting use value into exchange value, has been used in this context. One of the things that has recently become the object of commodification by television and online media is children. Children are considered attractive to advertisers because they are relatively malleable and influenced by their surroundings, and can be used as an attraction for audiences because of their innocence. This study aimed to explore forms of commodification of children, especially in the viral context of Farar Labadjo or who is known to the public as Fajar Sadboy. To understand this form of commodification, this research adopted the basic theory of media political economy proposed by Vincent Mosco. The research method used in this research was critical discourse analysis developed by Norman Firclough. A qualitative approach with descriptive research type was used in this research. The results of this study revealed various forms of commodification of children in television showed and online media based on the theory of media political economy. In this context, children were exploited and forced to perform various activities in order to fulfill the demand for content in the program. Besides that, Children are also used as a tool to increase advertising rates and get a share of the profits for program owners. One of the most striking forms of commodification is the large number of similar programs that invite children because there is an exchange value from the large number of viewers and increased content traffic. This study concludes that there are various forms of commodification in Television and Online Media programs effectively "commodifying" children's virility and even taking advantage of controversies and tragic incidents for profit.